2020
DOI: 10.4111/icu.2020.61.s1.s57
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use, immunosuppressive, chronic pain, and psychiatric conditions are prevalent in women with symptomatic mesh complications undergoing mesh removal surgery

Abstract: To identify demographic and clinical characteristics of patients with symptomatic pelvic floor mesh complications who underwent mesh removal at our academic medical center. The secondary goal was to determine patient-reported outcomes after mesh removal. Materials and Methods: We conducted a retrospective review of consecutive patients from 2011-2016 undergoing removal of mesh graft for treatment of symptomatic mesh-related complications. Patient demographics, comorbidities, symptoms, and mesh factors were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The heterogeneity of pain measurement and small cohort sizes make the comparison of studies and determination of optimal treatment difficult. Nevertheless, other studies also found a reduction in pain after MUS removal [ 20 , 21 , 22 ]. In our series, partial vaginal and complete vaginal MUS removal showed no significant difference in both pain scores and rates of recurrent SUI, which was also reported by Jambusaria et al [ 24 ].…”
Section: Discussionmentioning
confidence: 93%
“…The heterogeneity of pain measurement and small cohort sizes make the comparison of studies and determination of optimal treatment difficult. Nevertheless, other studies also found a reduction in pain after MUS removal [ 20 , 21 , 22 ]. In our series, partial vaginal and complete vaginal MUS removal showed no significant difference in both pain scores and rates of recurrent SUI, which was also reported by Jambusaria et al [ 24 ].…”
Section: Discussionmentioning
confidence: 93%
“…Other study designs have also suggested poor health outcomes. A large Canadian database cohort study found higher risks of depression and self-harm in women who required a surgical intervention for complications after a mid-urethral mesh sling procedure; 21 a retrospective case series review found a high prevalence of psychiatric and chronic pain conditions in patients undergoing mesh removal; 22 and a qualitative study of women presenting to a tertiary care clinic with complications relating to vaginal mesh found that these complications caused both physical and emotional pain. 23 The latter study suggested that women’s experiences followed different trajectories: some women experienced worsening health problems, anxiety and desperation, others who once considered themselves healthy, believed themselves unhealthy and adjusted their views accordingly, and a minority of women described a return to health.…”
Section: Discussionmentioning
confidence: 99%
“…Variables attempted to be extracted from the electronic patient files were age at time of revision surgery, gender, BMI, smoking, pain scores (using Numerical Rating Score (NRS) or Visual Analogue Scale (VAS)), postmenopausal state, sexual activity, vaginal deliveries in the past, number of abdominal surgeries in the past, amount of time between mesh placement and removal, a foreign body feeling, presence of neuropathic pain, comorbidities (including pain syndromes and/or systematic auto-immune disease), duration of presence of pain, use of NSAIDs and/or opioids, type of mesh implant, exposure of mesh, percentage of the mesh removed, number of revision surgeries, intraoperative macroscopic presence of a meshoma, and patients’ description of his/her clinical situation (normal, mild, moderate, severely or intense pain). Selection of parameters was based on prognostic factors for developing postoperative pain described in available published literature [ 2 , 9 , 12 , 14 , 16 18 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier research in both medical fields has signaled several predictors and patient characteristics that can aid in predicting whether reoperation will lead to beneficial results. However, since the list is neither exhaustive nor specified for mesh removal, more research is necessary to draw conclusions [16][17][18].…”
Section: Introductionmentioning
confidence: 99%